Processo educacional no ensino de Ciências e Biologia na perspectiva da Astrobiologia - Athayde, Saladina Amoedo (2015)
This paper presents a proposal of educational process, developed through applied research in order to seek the improvement about teaching Science and Biology in Basic School implementing current themes and concepts, interrelated to cross-cutting issues, going back to the origin of life, living beings, their interaction with the physical environment and the prospects for life elsewhere other than Earth. The project had as target students from elementary and high school from two public schools in the district of Feira de Santana-BA. It is justified by the low rates of our schools PISA (Programme for International Student Assessment) and IDEB (Education Development Index Basic) evaluations. The Vigotsky Knowledge Theory and Ausubel Learning Theory were used to guiding the educational process and pedagogical actions. Questionnaires were used as a data collection tool and the structured work by the construction and application of four activities, developed from the perspective of life on Mars. The choice of this planet is because of its importance for the study and teaching of astronomy through discoveries made since the first civilizations in search of understanding about planetary evolution and pre and post biotic ecosystems. Data analysis showed satisfactory results, it was possible to detect an improvement in the recognition of current concepts as a source of technological knowledge and as a result it expected to occur changes on educational indicators. Due to dissemination among teacher were demand applications in schools out of the winning ones, allowing viewing this proposal as reference in the quest for improving the teaching of Science and Biology.